RANCANG BANGUN SISTEM INFORMASI KEANGGOTAAN DAN PORTAL BERITA BERBASIS WEBSITE PADA UKM UNIVERSITAS PAMULANG SCOOTER - Muhammad Khoirun Nasikhin; Ardianto Moenir (CV. Multi Kreasi Media, 2022)
This study aims to produce a software design for membership information systems and website-based news portals at Students Scooter Organization of Pamulang University that is able to manage incoming member data, outgoing member data, search for member data, create news portals and centralize data in an integrated database. This type of research is Research and Development. The software development method uses the Waterfall Model. Software testing is done using black box and white box testing. Testing is done through validity and reliability tests. Data collection techniques in the study used interviews and questionnaires. The data analysis technique used descriptive qualitative analysis. The results showed that the Design and Build of Membership Information Systems and Website-Based News Portals at Students Scooter Organization of Pamulang University was able to manage incoming member data, outgoing member data, search for member data, create news portals and centralize data in an integrated database using collaboration between programming languages. PHP, mysql and XAMPP.